ASME 2011 Conference on Smart Materials, Adaptive Structures and Intelligent Systems, Volume 1 2011
DOI: 10.1115/smasis2011-5012
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuned Polymer Nano-Composite Coatings for Use in Geothermal Plants

Abstract: Often times erosion, corrosion, and fouling by scale deposition are primary issues for geothermal-fluid-wetted process equipment. In particular, wet heat exchangers used in geothermal power plants must deal with scale deposition. Previously, a surface-coating of polytetrafluoroethylene (PTFE) was considered to provide a non-stick surface. However, intrinsically poor thermal conductivity of PTFE, along with its poor abrasion resistance and weak adhesion to metal substrate, turns out to be a serious concern for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition to that, it enhances the thermal conductivity, corrosion resistance, and abrasion resistance of heat exchangers [31]. Keshri et al had studied CNT-reinforced aluminium oxide coatings for marine and high temperature turbine coating applications and observed a 30 % reduced wear loss due to the reinforcement of 8 wt% of CNT's [32].…”
Section: Advanced Coating Materials For Energy Applicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to that, it enhances the thermal conductivity, corrosion resistance, and abrasion resistance of heat exchangers [31]. Keshri et al had studied CNT-reinforced aluminium oxide coatings for marine and high temperature turbine coating applications and observed a 30 % reduced wear loss due to the reinforcement of 8 wt% of CNT's [32].…”
Section: Advanced Coating Materials For Energy Applicationsmentioning
confidence: 98%
“…In geothermal-based energy systems, Cheng et al had reported for carbon nanotube (CNT)/polytetrafluoroethylene (PTFE) composite coatings on heat exchanger which acts as an efficient super hydrophobic coating [31]. In addition to that, it enhances the thermal conductivity, corrosion resistance, and abrasion resistance of heat exchangers [31].…”
Section: Advanced Coating Materials For Energy Applicationsmentioning
confidence: 98%